Stenting of the right ventricular outflow tract with subsequent radical correction in a child with a tetralogy of Fallot: results of six-year follow-up - A. A. Lyapin; I. K. Khalivopulo; P. A. Shushpannikov; R. S. Tarasov (Фундаментальная и клиническая медицина)
Tetralogy of Fallot (ToF) is the most common cyanotic congenital heart defect. Since the first radical correction in 1954, treatment strategy has been constantly improving. Current treatment of ToF ensures the long-term survival (30-year survival ranges from 68.5% to 90.5%), yet it is still challenging in underweight patients. Here we present a clinical case of two-step surgery which included right ventricular outflow tract (RVOT) stenting and further radical correction in an underweight child who was then followed-up for six years. RVOT stenting is an appropriate alternative to the bypass surgery which has higher risk of perioperative complications. RVOT stenting significantly reduces hypoxia, enhances the development of the pulmonary vasculature and increases end-diastolic index ultimately permitting efficient radical correction after 4 months. The described approach resulted in a favorable outcome and quality of life after 6 years of follow-up.